Cardiorespiratory Fitness Is an Indicator of Arterial Stiffness and Aortic Blood Pressure in Healthy Adolescents - Hwan Kim; Scott R. Collier; Valerio Bonavolontà; Austin Lassiter; Seaver Wait; Marco Meucci (Children)
Background/Objectives: We aimed to investigate the influence of cardiorespiratory fitness (CRF) and body composition on arterial stiffness. Methods: Carotid-to-femoral pulse wave velocity (cfPWV) and aortic systolic (ASBP) and diastolic (ADBP) blood pressure were compared between upper and lower tertiles of oxygen consumption at the aerobic threshold (VO2AerT), peak oxygen consumption (VO2peak), percentage of fat mass (FM%), and body mass index (BMI) in sixty adolescents (30 males and 30 females, 14.9 ± 2.1 years old). A stepwise multivariable linear regression analysis was performed to investigate the independent associations between VO2AerT and VO2peak and cfPWV, and between BMI and FM% and cfPWV with adjustments for age, sex, ASBP, and ADBP. Results: cfPWV and ADBP were lower in the second and third VO2AerT tertiles compared to the first tertile (cfPWV, 4.7 ± 0.5 and 4.7 ± 0.5 vs. 5.3 ± 0.8 m/s, p < 0.01; ADBP, 62 ± 7 and 62 ± 7 vs. 70 ± 8 mmHg, p < 0.01). ASBP was lower in the third VO2AerT tertile compared to the first tertile (94 ± 7 vs. 101 ± 12 mmHg, p = 0.05). ADBP was lower in the second VO2peak tertile compared to the first tertile (62 ± 7 vs. 68 ± 9 mmHg, p = 0.03). ASBP was lower in the first and second BMI tertiles compared to the third tertile (95 ± 8 and 95 ± 7 vs. 102 ± 11 mmHg, p = 0.02). The eight-variable model significantly contributed to the variance of cfPWV (F(8, 51) = 7.450, p < 0.01), accounting for 47% of the variance. Individually, age (p < 0.05) and ADBP (p < 0.01) significantly predicted cfPWV. Conclusions: Submaximal indicators of CRF such as VO2AerT should be considered as a part of the risk stratification of cardiovascular disease in healthy adolescents.